Burnout syndrome – A professional hazards of Anaesthesiologists - Hossain, Md Mozaffer (Journal of the Bangladesh Society of Anaesthesiologists, 2020)
Abstract Not Available Journal of Bangladesh Society of Anaesthesiologists 2015; 28(1): 1-3